Handbook of motivation and cognition. Vol. 3, the interpersonal context - Sorrentino, Richard M; Higgins, E. Tory (Guilford Press, 1996)
University of Western Ontario, Canada. Third volume of a reference on the theories and research of motivation. Discusses the role of motivation and cognition in interpersonal and group situations. 42 contributors, 30 U.S.
Keywords: motivace; Motivation; psychologie, klinická psychologie; Psychology; psychologie